PERANCANGAN SISTEM AKSES PINTU OTOMATIS MENGGUNAKAN RFID CARD - Risdani Mu'arif Mu'arif (LKP KARYA PRIMA KURSUS, 2023)
Security systems that are part of a home, in particular, may still rely on manual locking, i.e. using standard locks as most people do. However, as technology advances, the application of microcontrollers to security systems can now be realized through the use of electronic devices as an alternative to traditional key security systems. This automatic door security system is designed to cover the inefficiencies of traditional door security systems which still use physical keys with dimensions that are still quite large and also require a longer time to open the door. Since RFID is a new technology along with the advancement of integrated circuit technology, it is certain that RFID can be used in various fields. The purpose of this research is to make it easier to access the door automatically by attaching an ID card to an RFID reader making it easy to open the door. Utilizing electromagnetic technology, users can use RFID as a user ID. Research and development is the research method used. Using Radio Frequency Identification (RFID) as a carrier for radio frequency wave data, the Arduino application creates a security system for this automatic door. This security system will be received by the recipient of the RFID Label or Tag known as a transponder, whose function is similar to a barcode. Keywords: Automatic Door, System, ID Card, RFID, Arduino